The Impact of Blended Learning on Cognitive and Affective Outcomes in Fiqh Education - Imran Rido; Muhammad Amin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to examine the impact of Blended Learning on students' cognitive and affective outcomes in Fiqh education at Madrasah Aliyah Irsyadul Islamiyah Bagan Batu. The research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The participants consisted of 60 students divided into an experimental class and a control class. Data were collected through cognitive tests, affective questionnaires, and documentation. The data were analyzed using validity and reliability tests, normality and homogeneity tests, correlation analysis, and Independent Sample t-test with the assistance of SPSS 25. The findings revealed that the implementation of Blended Learning significantly improved students' cognitive and affective learning outcomes. The cognitive variable obtained a significance value of 0.000 < 0.05 with a correlation coefficient of 0.768, indicating a strong relationship. Meanwhile, the affective variable showed a significant value of 0.001 < 0.05 with a correlation coefficient of 0.721, also categorized as strong. These results indicate that Blended Learning effectively enhances students' understanding of Fiqh concepts, learning motivation, discipline, responsibility, and active participation in learning activities. This study contributes theoretically by strengthening constructivist and social learning theories in Islamic education and practically by providing innovative digital learning strategies for improving the quality of Fiqh instruction in the digital era.